Implementation Of Ontology, Epistemology, And Axiology In Management Science - Adinda, Jihan; Alkasyah, Rafly; Razan, Nabilah; Salsabila, Fathia (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2025)
This article analyzes the implementation of the philosophy of science epistemology, ontology, and axiology in management science through a literature review. The findings show that epistemology provides guidance regarding validity and data collection methods, ontology helps in understanding the nature of organizational reality, and axiology ensures that research is conducted ethically and makes significant practical contributions. Methodological approaches commonly used in management research, such as positivism, post-positivism and mixed methods, demonstrate the relevance of scientific paradigms in understanding organizational complexity. The implications of these findings include contributing to the development of new paradigms in management science and providing practical guidance for more valid, relevant, and ethical research. The article confirms that philosophy of science not only builds theoretical foundations, but also enhances the quality of management research, enabling the development of scientific work that benefits both the academic community and organizational practice. Recommendations are given for integrating philosophy of science in research education and training to improve the relevance and impact of future research outcomes.